Coping Stress on Seafaring Wives Who Live Long Distance Marriage Relationships: Coping Stress pada Istri Pelayar yang Menjalani Relasi Pernikahan Jarak Jauh - Berliantin, Ajeng Riefa; Ansyah, Eko Hardi (Psikologia : Jurnal Psikologi, 2021)
The purpose of this study was to determine the stress coping of wives undergoing long-distance marriages. The research method uses qualitative methods with a phenomenological approach. Subjects in this study were two wives whose husbands left to work for more than 8 months and had small children. Retrieval of data in this study using the interview method and field notes to each respondent. The results showed that there was coping stress in sailing wives who had long-distance marriages, namely the physical, psychological and social aspects which were stress factors for the wife. The subject's effort to cope with stress is a form of stress coping. The forms of stress coping used by the two subjects were problem focused coping and emotional focused coping in which the subject did problem solving and get closer to God.